The Interpretive Function: To Be or Not to Be, That is the Question - Agerbo, Heidi (Lexikos, 2017)
Approximately a decade ago, it was suggested that a new function should be added to the lexicographical function theory: the interpretive function. However, hardly any research has been conducted into this function, and though it was only suggested that this new function was relevant to incorporate into lexicographical theory, some scholars have since then assumed that this function exists, including the author of this contribution. In Agerbo (2016), I present arguments supporting the incorporation of the interpretive function into the function theory and suggest how non-linguistic signs can be treated in specific dictionary articles. However, in the current article, due to the results of recent research, I argue that the interpretive function should not be considered an individual main function. The interpretive function, contrary to some of its definitions, is not connected to acting and therefore the only difference between reception and interpretation is that they work with different types of sign. However, the type of sign is not relevant for a function, or rather, it should not be a criterion for distinguishing between functions. The lemma selection for the communicative, cognitive as well as the operative functions could and should include linguistic as well as non-linguistic signs. Thus, theoretically, there is no reason to identify a fourth dictionary function as suggested by Tarp (2008), and practically, the development of modern technologies has diminished the distance in the treatment of different types of sign, making it easier for lexicographers to lemmatise non-linguistic signs. Concerning the point that non-linguistic signs are also worthy of lexicographical attention, my suggestion from 2016 still stands, the difference in this contribution being that the interpretive function is not considered an individual function.